Aisyiyah dan Peranannya dalam Meningkatkan Derajat Kaum Perempuan - Remiswal Remiswal; Suryadi Fajri; Rahmadina Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT This study aims to describe the role of Aisyiyah in improving the status of women in Indonesia from 1917-1945. This study uses a library research method using a philosophical approach and a historical approach. The results of this study indicate that Aisyiyah is a Muhammadiyah women's organization which was founded on 27 Rajab 1335 H, coinciding with 19 May 1917 M. The embryo of the establishment of Aisyiyah has been started since the Sapa Tresna association was held in 1914, namely an association of educated girls around the village of Kauman. . Nyai Dahlan's attention to Islamic education is very large. Like Ahmad Dahlan, Nyai Dahlan agreed on a formal term known as